CONTRASTIVE ANALYSIS BETWEEN INDONESIAN AND ENGLISH REPORTED SPEECH - AVIKA, - - (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Contrastive Analysis, Reported Speech. Indonesian and English have many differences in sentence structure. In this study, the researcher conducted research about contrastive analysis between Indonesian and English reported speech. The aim of this study is finding the differences and similarities between Indonesian and English reported speech patterns. This study used qualitative research and descriptive study to contrast the theories between Indonesian and English reported speech. Six textbooks related to English reported speech theories and a novel were used as the data in English, while data in Indonesian were three textbooks, an article, and a novel. This study reveals that there are more differences rather than similarities between those both languages. There are twelve differences, namely: 1) English has four general report sentences patterns while Indonesian has three; 2) reporting question; 3) reporting yes/no question; 4) reporting negative sentence 5) the adverb of place; 6) demonstrative adjective; 7) the tenses; 8) the adverb of time; 9) the modals;10) reporting suggestion; 11) –ing clause; 12) to-infinitive. The researcher has foundsome similarities namely: 1) no quotation marks; 2) the change of pronouns; 3) theintonations; 4) reporting prohibition; 5) reporting order; 6) the use of say and tell; 7)the entire quotation is in form of report sentence. Since the differences of the patternsare more than the similarities, it is predicted that Indonesian learners of English willface some difficulties in learning reported speech. The researcher suggests Indonesian learners of English focus on the differences in order to master reported speech deeply. The researcher recommends the teachers to understand the differences which enable them to teach reported speech. For the next researchers, it is recommended to conduct contrastive analysis in Indonesian and English with different topic or between other languages.